Influence of Hydrogen Bonding on the State Diagram of Cryoprotective Solutions - Sevastianov, Stanislav S.; Osetsky, Aleksandr I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2015)
N/A